Voltage-gated Ca(2+) channels and intracellular Ca(2+) release regulate exocytosis in identified rat corticotrophs - Tse, Amy (Blackwell Science Inc, 2000)
1. The patch clamp technique was used in conjunction with a fluorescent Ca(2+) indicator (indo-1, or indo-1FF) to measure simultaneously cytosolic Ca(2+) concentration ([Ca(2+)](i)) and exocytosis (changes in membrane capacitance) in single, identified rat corticotrophs. 2. Exocytosis could be stimulated by extracellular Ca(2+) entry (via voltage-gated Ca(2+) channels). A train of depolarizations could exhaust the pool of readily releasable granules and the pool replenished with a time constant of 42 s (at 22–25 °C). 3. Recordings from cells with 0.5 mm intracellular cAMP showed that the amplitude of the depolarization-triggered exocytosis, the Ca(2+) sensitivity of exocytosis, as well as the rate of replenishment of the readily releasable pool, were similar to the controls. 4. Exocytosis could also be stimulated by intracellular Ca(2+) release from the inositol 1,4,5-trisphosphate (IP(3))-sensitive store (via flash photolysis of caged IP(3)). At comparable [Ca(2+)](i), extracellular Ca(2+) entry and intracellular Ca(2+) release had similar efficacy in triggering exocytosis. 5. The rate of exocytosis triggered via depolarization or intracellular Ca(2+) release was much faster than that triggered via uniform elevation of [Ca(2+)](i) (Ca(2+) dialysis or flash photolysis of caged Ca(2+)). 6. The above findings suggest that both intracellular Ca(2+) release and voltage-gated extracellular Ca(2+) entry generate a spatial Ca(2+) gradient, such that the local [Ca(2+)] near the exocytic sites was ∼3-fold higher than the mean cytosolic [Ca(2+)]. However, neither cAMP nor the spatial Ca(2+) gradient generated during depolarization could account for the high efficacy of corticotropin-releasing hormone (CRH) in stimulating adrenocorticotropic hormone (ACTH) secretion from corticotrophs.